Community participation in clinical health research - a new research paradigm - Janet Frohlich; Annatjie Botes; Marie Muller (AOSIS, 2001)
The idea of community participation in health and research can be found in all major international and national declarations, including South Africa. Opsomming Gemeenskapsbetrokkenheid in gesondheid en in navorsing word internasionaal en nasionaal, insluitende Suid-Afrika, in verskeie verklarings van voorneme gereflekteer. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.